The impact of labor participation on older adults' well-being in active aging: A cross-sectional study in Hebei Province, China - Li, Xia; Noradilah, Md Nordin (Arts and Science Press Pte., 2024)
The active aging model has sparked discussions about improving the participation of older adults in the workforce and their overall well-being. This has led to a greater emphasis on providing continuous learning opportunities, offering flexible work arrangements, and creating health programs specifically tailored for this demographic. Therefore, the main purpose of this study is to investigate the association between labor participation and subjective well-being and to identify important factors that influence subjective well-being in older adults. The measurement of subjective well-being encompassed two key dimensions (i.e., life satisfaction and depression). The study recruited 202 elderly individuals in Hebei Province, China, through a cross-sectional method. Our findings revealed that the percentage of elderly individuals participating in the workforce was relatively low. There was a notable positive association between labor participation and life satisfaction. Additionally, labor participation and educational attainment are found to be significantly associated with life satisfaction among older adults. In summary, the findings of this study are essential for providing ideas to promote healthy aging and optimize the allocation of human resources.